2014
DOI: 10.3390/s140813830
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Sounds Acquisition Using Smartphones

Abstract: Tracheal sounds have received a lot of attention for estimating ventilation parameters in a non-invasive way. The aim of this work was to examine the feasibility of extracting accurate airflow, and automating the detection of breath-phase onset and respiratory rates all directly from tracheal sounds acquired from an acoustic microphone connected to a smartphone. We employed the Samsung Galaxy S4 and iPhone 4s smartphones to acquire tracheal sounds from N = 9 healthy volunteers at airflows ranging from 0.5 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Several previous studies have reported that the relationship between air flow and breath sound amplitude is linear under high flow rate conditions [27,33]. It has also been reported that the sound amplitude during inspiration is proportional to the square of the air flow at the mouth [34,35]. Moreover, it was shown that the flow profile of inhalations can be estimated based on the logarithmic relationship between the acoustic envelope of the inhalation sound and the flow volume [28].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported that the relationship between air flow and breath sound amplitude is linear under high flow rate conditions [27,33]. It has also been reported that the sound amplitude during inspiration is proportional to the square of the air flow at the mouth [34,35]. Moreover, it was shown that the flow profile of inhalations can be estimated based on the logarithmic relationship between the acoustic envelope of the inhalation sound and the flow volume [28].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this shape is that it provides an efficient transducer of air pressure fluctuations from the skin over the trachea to the microphone [ 27 ]. The acoustic sensor used in this study was developed by our colleagues at the Metropolitan Autonomous University at Mexico City, Mexico, and have been successfully applied for respiratory sound acquisitions [ 18 , 25 , 28 ]. The acoustic sensor was connected to the audio jack of the Samsung Galaxy S4 smartphone (Samsung Electronics Co., Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…They have fast microprocessors, large storage capacities and a lot of media capabilities. In addition, the mobility of the smartphones is making them more popular for usage outside the clinics or research facilities, when they can be used for measuring vital signs and health monitoring, as shown in some of the previous works of our research group [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the development of mobile technology has significantly evolved and is often used by clinicians for data acquisition and diagnosis. A study by Reyes et al 146 proposes the use of smartphones to acquire tracheal sounds. These researchers used two smartphones with different operating systems (Android and Apple iPhone operating system).…”
Section: A Toward Mobile Signal Acquisitionmentioning
confidence: 99%